Tindak Pidana Korupsi Yang Dilakukan Oleh Notaris Atas Penyalahgunaan Wewenang Dalam Penerbitan Covernote Untuk Pencairan Kredit (Studi Putusan Pengadilan Tinggi Medan Nomor 9/Pid.sus-Tpk/2023/Pt.mdn) - Siti Nabila, Marcellina (UI Scholars Hub, 2025)
This paper analyzes the role of covernotes in credit agreements and the consequences of notaries' abuse of authority, leading to corruption. This paper uses a doctrinal research method. A covernote is a written statement containing a notary's promises or commitment to complete their duties, regarding requirements that have not been met by the parties to issue a deed. The Law on Notary Publics does not contain any regulations or mention of covernotes. The existence of covernotes arises from the urgent need for banks to provide temporary documentation for executing credit agreements. Bank Indonesia Regulation Number 20/8/PBI/2018 concerning the Loan-to-Value Ratio for Property Loans, the Financing-to-Value Ratio for Property Financing, and Down Payments or Motor Vehicle Financing specifically authorizes notaries to issue covernotes. In carrying out their duties and authorities, notaries must adhere to the Law on Notary Publics and the Notary Code of Ethics. In carrying out legal acts, notaries are responsible for all their actions. If a notary commits an act that violates the law, they can be held accountable for their mistakes, whether administratively, under the code of ethics, civil law, or criminal law. If a notary's actions result in financial losses to the state, they can be charged with corruption.